1985
DOI: 10.1136/oem.42.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function of London firemen.

Abstract: ABSTRACr In a longitudinal study of a sample of firemen in London 1006 firemen were interviewed and examined in 1976

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…The cohort study by Musk et al (79), for example, showed a standardized mortality ratio of 93, 83 for active firefighters and 101 for retired firefighters, which is well within the expected range. Significant abnormalities in pulmonary function have been reported in current firefighters among smokers only (28), and even that seems to represent minimal small airways disease in asymptomatic firefighters employed for at least 25 years (63). Thus, the weight of evidence suggests that firefighters are not at greatly increased risk of chronic respiratory disease unless they experience an unusual exposure (82,126).…”
Section: Pulmonary Diseasementioning
confidence: 99%
“…The cohort study by Musk et al (79), for example, showed a standardized mortality ratio of 93, 83 for active firefighters and 101 for retired firefighters, which is well within the expected range. Significant abnormalities in pulmonary function have been reported in current firefighters among smokers only (28), and even that seems to represent minimal small airways disease in asymptomatic firefighters employed for at least 25 years (63). Thus, the weight of evidence suggests that firefighters are not at greatly increased risk of chronic respiratory disease unless they experience an unusual exposure (82,126).…”
Section: Pulmonary Diseasementioning
confidence: 99%
“…Many firemen retired as a result of respiratory diseases. In a different study of London firemen older than 40 years of age, declines in FEV 1 and FVC were found to be faster (27). Relationships were found between the duration of work and FVC, smoking and FEV 1 and FEF50, and smoking and duration of working and FEF75 declines (28).…”
Section: Discussionmentioning
confidence: 89%
“…According to a study, the highest decline in FEV 1 due to acute, intense exposure to fire smoke occurred in the first year, while the decline has been shown to continue l 6 years later (26). In another study, the decline of FEV 1 and FVC was faster in patients older than 40 years of age (27). A relation was found between the duration of the study and FVC, between tobacco use and FEV 1 and FEF50 and the duration of the study and declines in FEF75 (28).…”
Section: Introductionmentioning
confidence: 98%
“…9 This concern has been compounded by mortality and morbidity studies of fire fighters, which, although they have produced inconsistent evidence, have raised the possibility of increased risks of cardiovascular disease, respiratory disease, and cancers of the nervous, hematopoietic/lymphatic, respiratory, and gastrointestinal systems, which may be attributable to exposures to the components of smoke. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Several recent studies have suggested an increased risk of brain cancer among Washington fire fighters; brain, prostrate, colon, and lung cancer among Los Angeles fire fighters; and digestive tract cancers. 19,21,23,26 As a guide to the evaluation of the hazards posed by workplace exposures, NIOSH field staff employ environmental evaluation criteria for the assessment of a number of chemical and physical agents.…”
Section: Evaluation Criteriamentioning
confidence: 99%